1987
DOI: 10.1111/j.1432-1033.1987.tb13711.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C potentiates isoproterenol‐mediated cyclic AMP production without modifying the homologous desensitization process in J774 cells

Abstract: The J774 murine macrophage cells possess a P2-adrenergic receptor coupled to adenylate cyclase, which can be regulated by homologous desensitization. Stimulation of protein kinase C by phorbol esters or oleoyl acetyl glycerol potentiates two-to-threefold the isoproterenol-induced cyclic AMP accumulation. These promoters act at a post-receptor level, since the number and affinity of the P-adrenergic receptors, measured by use of the hydrophilic ligand [3H]CGP-12 177, are not modified. In addition, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Preincubation of the cells with OAG resulted in a potentiation of the stimulatory effect of PGEl on cAMP production (Fig. 71, as was described for isoproterenol (Chambaut-Guerin and Thomopoulos, 1987). Under the same experimental conditions, PGEl-induced adhesiveness was clearly inhibited by preincubation with OAG (data not shown).…”
Section: Effect Of Oag On Hormone-stimulated Camp Productionsupporting
confidence: 67%
See 2 more Smart Citations
“…Preincubation of the cells with OAG resulted in a potentiation of the stimulatory effect of PGEl on cAMP production (Fig. 71, as was described for isoproterenol (Chambaut-Guerin and Thomopoulos, 1987). Under the same experimental conditions, PGEl-induced adhesiveness was clearly inhibited by preincubation with OAG (data not shown).…”
Section: Effect Of Oag On Hormone-stimulated Camp Productionsupporting
confidence: 67%
“…71, as was described for isoproterenol (Chambaut-Guerin and Thomopoulos, 1987). Under the same experimental conditions, PGEl-induced adhesiveness was clearly inhibited by preincubation with OAG (data not shown).…”
Section: Stimulation Of Adhesiveness By Kinase a Andmentioning
confidence: 58%
See 1 more Smart Citation
“…Protein kinase C has been shown to modulate the function of several G-protein-linked receptors, and consensus sites for phosphorylation have been identified in many of these receptors. Although a few early studies suggested that activation of protein kinase C desensitizes the ␤ 2 -adrenergic receptors (38,39), most subsequent studies reported either no effect of protein kinase C activation on desensitization (40,41) or frank potentiation of ␤ 2 -adrenergic receptor signaling rather than desensitization (42)(43)(44)(45)(46)(47)(48). Protein kinase C is associated in complex with the receptor-gravin complex in unstimulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cAMP has been shown to inhibit phosphoinositide hydrolysis in platelets (2) and neutrophils (3), but it has no effect in monocytes (4). Conversely, activation of protein kinase C, one of the major consequences of phosphoinositide hydrolysis, has been reported to inhibit hormone-stimulated AC activity in some tissues (5)(6)(7)(8), while it potentiates AC activity in other tissues (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%